2009
DOI: 10.3181/0903-rm-105
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Treatment with Plasminogen Activator Inhibitor-1 Decoys Reduces Tubulointerstitial Fibrosis

Abstract: We examined the capacity of delayed inhibition of plasminogen activator inhibitor-1 (PAI-1) to reduce tubulointerstitial fibrosis induced by unilateral ureteral obstruction (UUO) in mice. Small peptides mimicking parts of urokinase (uPA) and tissular plasminogen activator (tPA) and serving as decoy molecules for PAI-1 were administered daily during the late stages (3 to 8 days) of UUO. Treatment with PAI-1 decoys reduced interstitial deposition of fibronectin, collagen III and collagen IV without changes in ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Within the Smad3 pathways, plasminogen activator inhibitor-1 (PAI-1), a potent profibrotic matricellular protein, is important in TGF-beta1 signaling and is involved in inflammatory and fibrotic pathways [1••, 3540] via suppression of ECM degradation and increased matrix remodeling [1••, 37]. TGF-beta1 also acts via free radicals on non-Smad pathways including the c-Src-EGFR-MEK-ERK cascade.…”
Section: Oxidative Stress and Tgf-betamentioning
confidence: 99%
“…Within the Smad3 pathways, plasminogen activator inhibitor-1 (PAI-1), a potent profibrotic matricellular protein, is important in TGF-beta1 signaling and is involved in inflammatory and fibrotic pathways [1••, 3540] via suppression of ECM degradation and increased matrix remodeling [1••, 37]. TGF-beta1 also acts via free radicals on non-Smad pathways including the c-Src-EGFR-MEK-ERK cascade.…”
Section: Oxidative Stress and Tgf-betamentioning
confidence: 99%
“…Mesangial expansion of DN, caused by the proliferation of mesangial cells (MCs) and the excessive accumulation of the extracellular matrix (ECM), is one of the pathological features of DN (2). Hyperglycemia, which activates multiple intracellular signaling factors and results in abnormalities in blood flow and the accumulation of ECM (3)(4)(5), has been confirmed as the main initiative factor in the etiology of DN (6), which is one type of kidney fibrosis disease (7)(8)(9). In the clinical settings, the major ECM proteins, including collagen type IV (ColIV) and fibronectin (FN), are regarded as the markers of fibrogenesis in numerous kidney fibrosis diseases, such as DN.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, these results support the notion that increased plasmin activity may play an important role in PAI-1 antisense ODN therapy limiting fibrosis. However, a recent study [27] demonstrated that treatment with PAI-1 decoy peptides reduced tubulointerstitial fibrosis in unilateral ureteral obstruction mice model without significant effect on plasmin activity but with increased PA activity along with hepatocyte growth factor (HGF) expression. The authors speculated HGF-dependent ECM degradation as an antifibrotic mechanism of PAI-1 decoy peptide.…”
Section: Discussionmentioning
confidence: 99%
“…Data from genetically modified mice such as PAI-1 overexpressed transgenic or null mice suggest PAI-1 as a therapeutic target for renal fibrosis. With respect to therapeutic interventions for renal PAI-1, mutant non-inhibitory PAI-1 peptide [17][18][19] and PAI-1 decoy peptide [27] have been used to block PAI-1 synthesis in vivo as well as in vitro. In the present study, phosphorothioate-modified PAI-1 antisense ODN was used to study the role of PAI-1 in primary cultured rat mesangial cells.…”
Section: Discussionmentioning
confidence: 99%